Designing Travel Aggregator Application Using the Integration of Fuzzy Electronic Service Quality and Fuzzy Refined Kano - Amanda Sucita Brahmana; Yati Rohayati (Institut Teknologi Sepuluh Nopember, 2020)
The rapid development of transportation business makes travel aggregator application needed by the community. One diversified multinational company in Indonesia has developed a travel aggregator application to make customers easier to choose travel according to their needs. However, application design does not meet the standards proven by a preliminary survey. Therefore, it is necessary to explore the user's needs for travel aggregator application. This research aims to identify True Customer Needs by using the integration of Fuzzy Electronic Service Quality and Fuzzy Refined Kano in order to improve accuracy of data. To ensure the quality of the application before it is released, there are 8 key dimensions of quality that used namely payment method, application design, ease of use, responsiveness, security & privacy, information quality, portability, and maintainability. Fuzzy Electronic Service Quality is used to measure the level of satisfaction using the Fuzzy questionnaire. Fuzzy Refined Kano is used to obtain categories namely attractive (A), must-be (M), one-dimensional (O), indifferent (I), reverse (R) and questionable (Q) on each attribute need with Fuzzy processing. Based on the integration, there are 22 attributes need with 14 strong attributes need that need to be improved. The improved attributes need is called True Customer Needs.